LOOKING AGAIN AT SPEAKING PRACTICE IN ENGLISH TEACHING - Ingrid Brita Mathew (Universitas Negeri Padang, 2015)
A review of the research on S/FL (second and foreign language) learning and teaching suggests that one current trend, of relevance of those of us teaching English in Indonesia in speaking classes, is a reconsidering of the role of repetition and drills in language practice.Use of communicative curricula does not call for less practice but rather different kinds of practice than previous behaviorist-based curricula. Much more time is needed for a new language habit to be formed than is often allorved for by teachers.At low levels, use of repetition is useful, indeed necessary. Drills based around language functions are relevant to a communicative curriculum. Controlled and free speaking practice of meaningful activities becoming increasingly personalized aids in the automatic production of new language items.Such practice will need to be done both in and out of class, in order for enough time and interaction in English to take place.